Adaptive therapy for cancer: Integrated modelling of tumoral competition for controlling drug resistance - Strobl, MAR (2021)
Treatment in advanced cancers often provides only temporary improvements due to the emergence of drug-resistant tumour subpopulations. Standard-of-care regimens seek to maximise cell kill in order to achieve a cure, but thereby inadvertently also free resistant cells from the intra-tumoral competition which usually constrains their growth. An emerging alternative strategy, called adaptive therapy (AT), aims to tackle this problem by prioritising tumour control over cure. The idea is to leverage intra-tumoral competition to slow, or even avoid, the expansion of resistance.